2012
DOI: 10.5005/jp-journals-10006-1183
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Pap Smear, Colposcopy and Histopathology in Women with Unhealthy Cervix

Abstract: Cervix cancer is one of the most common cancers in women after breast cancer. Pap smear and colposcopy are cornerstone for the diagnosis for premalignant conditions, though the specificity and sensitivity of each is different. Present study was conducted to see the correlation of coloposcopy, histopathology and Pap smear in low resource setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
(1 reference statement)
1
7
0
Order By: Relevance
“…Specificity of Pap smear and colposcopy ranging from 19.5%-98.71% vs 52%-93.4% respectively. 12,13,25,27,28 In the present study,overall Pap smear had a poor sensitivity compared to colposcopy, 29.7% vs 85.9 % respectively. Pap smear had a better specificity though not significantly compared to colposcopy, 94.4% vs 74.3 % respectively.…”
mentioning
confidence: 46%
See 1 more Smart Citation
“…Specificity of Pap smear and colposcopy ranging from 19.5%-98.71% vs 52%-93.4% respectively. 12,13,25,27,28 In the present study,overall Pap smear had a poor sensitivity compared to colposcopy, 29.7% vs 85.9 % respectively. Pap smear had a better specificity though not significantly compared to colposcopy, 94.4% vs 74.3 % respectively.…”
mentioning
confidence: 46%
“…The incidence of premalignant lesions of cervix in various studies range from 8.15% to 35.2%. 12,13,25,27,29,30 The main goal of cervical screening is to identify women with premalignant lesions of cervix which are precursors of invasive cancer and require treatment, thus ultimately decreasing morbidity and mortality due …”
mentioning
confidence: 99%
“…5 Pradhan B, mital V P et al showed in their study than CIN was more prevalent in age group of 41 to 50 years. 6 Ashmita D et al showed maximum patient of CIN between the age group 30 to 50 similar results were seen in following studies.…”
Section: Discussionmentioning
confidence: 80%
“…on CIN. 5 N gopal, prashant s joshi, showed increased incidence of CIN in para 2. 8 S sharma, M saini et al showed maximum CIN in para 2.…”
Section: Discussionmentioning
confidence: 93%
“…This is considered as a vital reproductive health problem in women and a prime cause of mortality among young women [1]. Global report published by WHO in 2014, shows almost 266000 women died from cancer of the cervix in the year 2012.…”
Section: Introductionmentioning
confidence: 99%